2011
DOI: 10.4037/ccn2011551
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Corticosteroids to Treat Septic Shock: A Critical Literature Review

Abstract: Septic shock is the 13th leading cause of death in the United States. The rate of severe sepsis nearly doubled and mortality increased more than 60% during the 10-year period ending in 2003. Systemic inflammatory response syndrome has noninfectious and infectious causes. Noninfectious ones include burns, trauma, severe pancreatitis, and therapy with monoclonal antibodies or immunomodulatory drugs such as interleukin 2. Progression from sepsis syndrome to septic shock is caused by a series of immune responses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Además, se ha demostrado que las citoquinas inflamatorias inducen una hiperactividad de la isoforma inducible de la óxido nítrico sintasa (iNOS), la cual provoca apoptosis de células neuroendocrinas, así como resistencia periférica a ACTH y CS. 4,5 Se han descrito además, ciertas reacciones medicamentosas que pueden alterar el eje en sepsis, una de las más importantes, se presenta con el uso del etomidato (anestésico no barbitúrico utilizado en el proceso de intubación) que inhibe la síntesis de cortisol, ya que inactiva la enzima 11β-hidroxilasa, la duración de este efecto perdura por 24-36 horas. Existen estudios que comparan el uso de etomidato versus ketamina en pacientes que requirieron intubación en presencia de SS documentándose mayor incidencia significativa de insuficiencia adrenal en los que utilizaron etimodato.…”
Section: Discussionunclassified
“…Además, se ha demostrado que las citoquinas inflamatorias inducen una hiperactividad de la isoforma inducible de la óxido nítrico sintasa (iNOS), la cual provoca apoptosis de células neuroendocrinas, así como resistencia periférica a ACTH y CS. 4,5 Se han descrito además, ciertas reacciones medicamentosas que pueden alterar el eje en sepsis, una de las más importantes, se presenta con el uso del etomidato (anestésico no barbitúrico utilizado en el proceso de intubación) que inhibe la síntesis de cortisol, ya que inactiva la enzima 11β-hidroxilasa, la duración de este efecto perdura por 24-36 horas. Existen estudios que comparan el uso de etomidato versus ketamina en pacientes que requirieron intubación en presencia de SS documentándose mayor incidencia significativa de insuficiencia adrenal en los que utilizaron etimodato.…”
Section: Discussionunclassified
“…This probably indicates the need for a larger clinical trial. [2] Current recommendations [3,11,12] suggest: • Administering intravenous corticosteroid therapy (200-300 mg/day) to adult patients with severe septic shock (defined as a systolic blood pressure less than 90 mmHg for more than 1 h despite both adequate fluid resuscitation and vasopressor administration); • Not administering the corticosteroid to patients without shock or patients with less severe shock (defined as those in whom fluid resuscitation and vasopressor therapy have restored hemodynamic instability); • ACTH test prior to administering steroids in sepsis is not recommended; • Typically administer hydrocortisone for 57 days and taper the dose as guided by the clinical response.…”
Section: Sirmentioning
confidence: 99%
“…[1] Progression of sepsis to septic shock is caused by series of immune responses. [2] For many decades in the past steroids have been used in the management of sepsis but there has been an ambiguity in their use in septic shock, doses, duration of therapy effectiveness. However, recent studies have shown it to be effective in septic shock associated with "relative adrenal insufficiency".…”
Section: Sirmentioning
confidence: 99%